A Bivalve Biomineralization Toolbox. (20th May 2021) - Yarra, Tejaswi; Blaxter, Mark; Clark, Melody S
Abstract: Mollusc shells are a result of the deposition of crystalline and amorphous calcite catalyzed by enzymes and shell matrix proteins (SMP). Developing a detailed understanding of bivalve mollusc biomineralization pathways is complicated not only by the multiplicity of shell forms and microstructures in this class, but also by the evolution of associated proteins by domain co-option and domain shuffling. In spite of this, a minimal biomineralization toolbox comprising proteins and protein domains critical for shell production across species has been identified. Using a matched pair design to reduce experimental noise from inter-individual variation, combined with damage-repair experiments and a database of biomineralization SMPs derived from published works, proteins were identified that are likely to be involved in shell calcification. Eighteen new, shared proteins likely to be involved in the processes related to the calcification of shells were identified by the analysis of genes expressed during repair in Crassostrea gigas, Mytilus edulis, and Pecten maximus . Genes involved in ion transport were also identified as potentially involved in calcification either via the maintenance of cell acid–base balance or transport of critical ions to the extrapallial space, the site of shell assembly. These data expand the number of candidate biomineralization proteins in bivalve molluscs for future functional studies and define a minimal functional protein domain set required to produce solid microstructures from soluble calcium carbonate. This is important for understanding molluscan shell evolution, the likely impacts of environmental change on biomineralization processes, materials science, and biomimicry research.